Is Digitalization Really Matter on SMEs? - Wardhani Rulyanti Susi; Ridwan Muhammad Qomaruddin; Bahri Alim (SHS Web of Conferences, 2025)
Digitalization has penetrated various sectors, including SMEs. This paper aims to empirically prove whether digitalization has an impact on the value-added and productivity of SMEs. Using the Innovation Theory by Rogers we analyze the perception of 156 SMEs who have digitized their business. The result says that there is enough evidence that digitalization has an impact on the productivity and value-added of SMEs. This evidence supports the Innovation Theory that digitalization can increase productivity and value-added in companies including SMEs by increasing operational effectiveness and efficiency. Stakeholders, especially the government must encourage SMEs to digitize their business by taking supportive policies and providing incentives for SMEs who digitize.